2011
DOI: 10.5507/bp.2011.029
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Syndromes Associated With Renal Cell Carcinoma - A Review

Abstract: Aims.A review of recent knowledge on heredital syndromes related to renal cell carcinoma. Methods. Aim of this review was to summarize the recent knowledge of genetic syndromes associated with renal cell carcinoma.Results. Summary of incidence and factors modulating risk of hereditary renal cell carcinoma development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Each of the known genes for RCC is involved in oxygen, iron, and energy or nutrient-sensing pathways in a way or another (Azeem et al, 2011;Jonasch et al, 2012;Linehan and Ricketts, 2013). In a recent epidemiologic study from Northern Europe, Haggstrom et al found that high levels of several metabolic factors, both separately and combined, were associated with an increased risk of RCC.…”
Section: Discussionmentioning
confidence: 99%
“…Each of the known genes for RCC is involved in oxygen, iron, and energy or nutrient-sensing pathways in a way or another (Azeem et al, 2011;Jonasch et al, 2012;Linehan and Ricketts, 2013). In a recent epidemiologic study from Northern Europe, Haggstrom et al found that high levels of several metabolic factors, both separately and combined, were associated with an increased risk of RCC.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, approximately 30% of RCC patients have metastatic lesions detected at initial diagnosis . The morbidity and mortality of RCC have still been growing up during the past several years . Due to its resistance to radiation‐ and chemo‐therapy and immunotherapy, surgical resection remains the unique curative treatment for RCC .…”
Section: Introductionmentioning
confidence: 99%
“…3 The morbidity and mortality of RCC have still been growing up during the past several years. 4 Due to its resistance to radiation-and chemo-therapy and immunotherapy, surgical resection remains the unique curative treatment for RCC. 5,6 Although tyrosine kinase inhibitor (TKI)-based antiangiogenic therapy is standard treatment for advanced RCC (aRCC) or metastatic RCC (mRCC) and improves the prognosis of patients, its effect remains limited because of drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…265731 individuals were diagnosed with renal caner and 113315 individuals died from this type of cancer in 2008 [2], [3]. More seriously, the morbidity and mortality of this type of cancer is still growing [4]. 90–95% of renal cell carcinoma arises from the kidney and the occurrence of tumors is associated with racial and ethnic characteristic [1].…”
Section: Introductionmentioning
confidence: 99%